PENGARUH GENDER FINANCIAL EXPERTISE KOMITE AUDIT TERHADAP PRAKTIK MANAJEMEN LABA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Flaviana Agustiani Yuniargo; Senny Harindahyani (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2021)
Earnings management is a manager's choice to choose accounting policies or real actions to achieve certain earnings goals. This study aims to examine the effect of the gender financial expertise of the audit committee on earnings management practices. This study uses 852 samples of non-financial companies listed on the Indonesia Stock Exchange in 2016-2018 by using multiple linear regression analysis with classical assumption testing. The result of this study is the indication that committee audit financial expertise (EXPERT), proportion of the number of women on the audit committee (ACFD), and proportion of female financial experts on the audit committee (FEMEX) do not have a significant influence on earnings management as measured by using discretionary accruals. On the contrary, the proportion of male financial experts on the audit committee (MALEX), has a significant positive effect on earnings management. This shows that the presence of financial expertise that affects earnings management has been influenced by the sex of male financial experts. This research is in accordance with the theory that reveals that there are different effects with the existence of gender differences in a company.